SEXUALLY TRANSMITED DISEASES: TO PRESERVE THE HUSBAND'SCONFIDENTIALITY OR TO PROTECT WOMAN'S HEALTH? - Janina Pontes Pisani; Elma Lourdes Campos Pavone Zoboli (Universidade Federal do Paraná, 2009)
To maintain the privacy and confidentiality of patients is a critical issue for ethics. We developed an exploratory,quantitative and qualitative study with potential users of the Unique Health System to identify how they expect that healthpersonnel would behave when one of the heterosexual partner has syphilis. Subjects were employees of a public University.Data collection was developed through an anonymous and self reported questionnaire, with questions about how the healthprofessional should behave when a husband with syphilis doesn't want his wife to know about the disease and ask the healthteam to get her examined without knowing about his problem. As results, interviewees expect the maintenance of confidentiality,leaving the husband in charge of telling his wife the truth. Health professionals are seen as a mediator of the situation, ofwhom they expect orientation and support in the revelation of health problems. To know what the patients expect from healthprofessionals could help nurses to deal with ethical situations that might be a problem among the issues of sexual health